Social Representations of Persons with Learning Disability or Autism Spectrum Disorder Among Rehabilitation Professionals in Sweden - Germundsson, Per (Développement Humain, Handicap et Changement Social / Human Development, Disability, and Social Change, 2018)
Individuals with disabilities are affected by their environment in different ways, and one important factor involves how these individuals are perceived by others. This article focuses on rehabilitation professionals and the social representations of people with learning disability or autism spectrum disorder, as this group’s life situation is largely influenced by the professionals who work with them in their everyday lives. An association study, which is an established method in the theory of social representations, was carried out to gain more insight; in total, 121 rehabilitation professionals were included in the study. The results indicate that, when thinking about the target group, the respondents often associated the individuals in the group with work and the working process. A relational representation emerges where the individual is not perceived as someone with independent agency but rather as a person whose characterization is assigned in relation to the work tasks. Despite this, the respondents were sympathetic to the individuals and this work. The study also shows that the professionals’ social representations of the target group differs depending on what organization they belong to and that the various denominations of the individuals used in the organizations are not appreciated by the professionals.